2002
DOI: 10.1111/j.1752-1688.2002.tb01550.x
|View full text |Cite
|
Sign up to set email alerts
|

FECAL‐INDICATOR BACTERIA IN STREAMS ALONG A GRADIENT OF RESIDENTIAL DEVELOPMENT1

Abstract: Fecal‐indicator bacteria were sampled at 14 stream sites in Anchorage, Alaska, USA, as part of a study to determine the effects of urbanization on water quality. Population density in the subbasins sampled ranged from zero to 1,750 persons per square kilometer. Higher concentrations of fecal‐coliform, E. coli, and enterococci bacteria were measured at the most urbanized sites. Although fecal‐indicator bacteria concentrations were higher in summer than in winter, seasonal differences in bacteria concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 15 publications
1
32
0
Order By: Relevance
“…In urban areas, the combination of extensive impervious surface cover and high density of storm drains promote the rapid flushing of bacteria from lawns, roads, and other surfaces into streams (Frenzel & Couvillion, 2002;Mallin et al, 2000). However, we have documented high concentrations of E. coli and total coliforms under baseflow, rather than storm flow, conditions.…”
Section: Urban Land Cover and Bacterial Abundancementioning
confidence: 73%
See 2 more Smart Citations
“…In urban areas, the combination of extensive impervious surface cover and high density of storm drains promote the rapid flushing of bacteria from lawns, roads, and other surfaces into streams (Frenzel & Couvillion, 2002;Mallin et al, 2000). However, we have documented high concentrations of E. coli and total coliforms under baseflow, rather than storm flow, conditions.…”
Section: Urban Land Cover and Bacterial Abundancementioning
confidence: 73%
“…Similar results have been found by studies in other regions. For example, Frenzel and Couvillion (2002) found that concentrations of E. coli, fecal coliforms, and enterococci were higher in stream sub-basins with higher human population densities in and near Anchorage, Alaska. Similarly, Mallin, Williams, Esham, and Lowe (2000) found that fecal coliform abundance correlated positively with human population density, percentage of developed land, and percentage of impervious surface in five tidal creek basins in North Carolina.…”
Section: Urban Land Cover and Bacterial Abundancementioning
confidence: 99%
See 1 more Smart Citation
“…The positive correlation of NO − 3 and agricultural land in the HPS region (located downstream) is consistent with many others studies (Hill 1978;Neill 1989;Johnson and Gage 1997;Tufford et al 1998). There are also weak positive and negative loadings on T, and E. coli temperature is most possibly related to seasonal effects, while E. coli is strongly related to municipal sewage and wastewater treatment plants (Frenzel and Couvillion 2002) are due to agricultural runoff such as livestock waste and fertilizers (Buck et al 2003), industrial effluents, municipal sewage, and existing sewage treatment plants because PO 3− 4 is an important component of detergents (Vega et al 1998). VF6 explains 4.9% of the total variance and has strong positive loading on coliform, while VF7 explained 5.8% of the total variance with strong loading on COD.…”
Section: Figmentioning
confidence: 99%
“…Fecal coliforms bacteria are found in the intestinal tract of humans and other hot-blooded animals. Although fecal coliform bacteria are not necessarily dangerous to men, their high concentrations in water bodies indicate hazards for the human health 1 . Thus, the monitoring of such concentrations consists of a method to identify contamination magnitude, and a very well calibrated mathematical model may be used to describe such pollution.…”
Section: Introductionmentioning
confidence: 99%